2020
DOI: 10.1186/s12891-020-03604-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of three minimally invasive fixations for unilateral pubic rami fractures

Abstract: Background: To compare the mechanical characteristics of a percutaneous superior pubic intramedullary screw, percutaneous bridging plate and percutaneous screw-rod system of the anterior ring for the treatment of unilateral vertical pubic fractures to provide a reference for clinical application. Methods: A finite element model of pelvic anterior ring injury (unilateral vertical pubic fracture) was produced. The fractures were fixed with a percutaneous superior pubic intramedullary screw, percutaneous bridging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, the dimension and trajectory of the cannulated screw must be considered with respect to morphological variations of the superior pubic ramus. Generally speaking, cannulated screws with a long length (>100 mm) and a small diameter (<6.5 mm) are no longer available owing to the pro risk of breakage 33 . However, even with a 6.5 mm screw, some patients did not have enough acetabular and parasymphyseal areas for safe placement 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the dimension and trajectory of the cannulated screw must be considered with respect to morphological variations of the superior pubic ramus. Generally speaking, cannulated screws with a long length (>100 mm) and a small diameter (<6.5 mm) are no longer available owing to the pro risk of breakage 33 . However, even with a 6.5 mm screw, some patients did not have enough acetabular and parasymphyseal areas for safe placement 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In pelvic surgery, prioritizing the treatment of posterior pelvic ring injuries takes precedence because maintaining stability in the posterior pelvic ring is essential [1][2][3]. While osteosynthesis of the anterior pelvic ring is generally regarded as less critical compared to its posterior counterpart, suboptimal reduction quality and stability may contribute to a reduction in the functional performance of patients [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Through mechanical experiments, researchers have confirmed that transpubic screws can maintain the stability of the anterior ring of the pelvis 8 . Based on its advantages of good mechanical stability and low trauma, transpubic screws are considered to be the best surgical method for pubic fracture 9 . An anatomic study of 260 transpubic screw corridors found that all males were able to accommodate the insertion of screws with a diameter of 6.5 mm, while 15% of females were unable to accommodate the insertion of screws with a diameter of 6.5 mm 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Based on its advantages of good mechanical stability and low trauma, transpubic screws are considered to be the best surgical method for pubic fracture. 9 An anatomic study of 260 transpubic screw corridors found that all males were able to accommodate the insertion of screws with a diameter of 6.5 mm, while 15% of females were unable to accommodate the insertion of screws with a diameter of 6.5 mm. 10 , 11 Most men could even accommodate the insertion of a 7.3 mm diameter screw.…”
Section: Introductionmentioning
confidence: 99%